High-test molasses or maize as energy source for growing pigs. Distribution studies of digesta under fasting conditions - Ly, Julio (Cuban Journal of Agricultural Science, 2016)
The digestive content of 14 Yorkshire x Landrace x Duroc castrated male and female pigs, of around 55 kg of liveweight, was examined. Animals were fed ad libitum since the 30 kg, with diets of high-test molasses or maize, as the only energy source. After the slaughter, before the daily distribution of food, the digestive content of the centripetal colon tended (P < 0.10) to be higher with maize than with high-test molasses, and it was significantly (P < 0.01) higher regarding the halves of small intestine and caecum, while the gastric content and the content of the centrifuge colon did not differ. In both diets, the centripetal colon determined significantly (P < 0.01) the highest percentage contribution of fresh digesta, 43.4 and 33.7 % for maize and high-test molasses, respectively. The digestive content of all the tract was higher (P < 0.10) in the maize diet than in the high-test molasses (52.1 and 43.1 g/kg of body weight, respectively). Under fasting conditions, for both diets, the large intestine contributed with almost two thirds of all the fresh digesta found in the food carcass. It is suggested that, in growing pigs fed ad libitum with a diet of high-test molasses, a lower content of fresh digesta may be associated with higher values of digestibility, and therefore, with lower empty weight of the food carcass.Key words: pigs, digesta, high-test molasses, maize